Beda Pengaruh Kondisi Kaki Datar dan Kaki dengan Arkus Normal Terhadap Keseimbangan Statis pada Anak Usia 8-12 Tahun di Kelurahan Karangasem, Surakarta (Lembaga Penerbitan Universitas Esa Unggul, 2009)
Equilibrium can be define as ability to mantaining center of gravity through base support when standing on one point. The objective of this study is to investigate the impact of flat foot and normal arch toward static equilibriumÂ on children agedÂ 8-12 in the Karangasem district of Surakarta. This research is categorized as non experiment survey research using 58 children aged 8-12 as samples which consists of 31 boys (14 child with flat foot condition and 17 child with normal arches condition) and 27 girls (10 child with flat foot condition and 17 child with normal arches condition). The research is using independent t test analyzed to compare score of static equilibrium on 2 group (boys and girls). The research results show that does not difference effect between boys and girls with flat foot and normal archus condition to static aquilibrium on children aged 8-12 in the Karangasem district of Surakarta.Keyword: Static Equilibrium, Flat Foot, Fallen Arches